Solitary abdominal wall hydatid cyst—a rare condition. Issue 12 (9th December 2022) - Kofina, Konstantinia; Papatheodorou, Nikolaos; Konomi, Michael; Giannopoulos, Ioannis; Valkanos, Anastasios; Karanikas, Michael
Abstract: Hydatid disease is a parasitic infection by a tapeworm of the genus Echinococcus that usually presents in the liver and lungs. Presentation of the disease as a solitary abdominal wall lesion, however, is a rare entity and only nine cases have been reported in the literature thus far. We present the case of a 53-year-old Caucasian female presenting with a mass located in the left flank that was proven to be a solitary hydatid cyst intraoperatively.